Mapping economic clusters using satellite imagery to assess the impact of transport corridors in CAREC countries - United Nations Economic; Social Commission for Asia; the Pacific; Syed M Hasan (Asia-Pacific Sustainable Development Journal, 2023)
Investment in transport infrastructure boosts regional economies. Transforming a transport corridor into an economic corridor depends on ensuring market linkages. Focusing on the CAREC transport corridors in the mainly landlocked Central Asian region, this study makes an assessment to determine if low transport costs result in a cumulative causation process leading to the emergence of economic clusters. Using satellite imagery and multiple criteria decision modelling, land-use intensity changes are mapped to identify potential sites for economic activities in China, Pakistan and Tajikistan are identified. The study’s findings can be used in the design of policy interventions and for future investments.